6 - Restructured Citizen–Government Relationship in Kenya’s 2010 Constitution and the Right of Hawkers to the City in Nairobi - Wangui Kimani, Esther; Gachigua, Sammy Gakero; Kariuki, George Mbugua (Africa Development, 2021)
This article interrogates how various actors in the Nairobi Central Business District (CBD) space have made sense of the 2010 Constitution’s expansive provisions on socio-political and economic rights to advance hawkers’ claims to the right to the city. Using Lefebvre’s and human rights notions of the ‘right to the city’, the study finds that the Constitution has immense potential to secure the hawkers’ right to the city. However, various challenges impede efforts towards its realisation. Firstly, the 2007 no-hawking-in-the-CBD bylaw exerts inordinate influence, in practice suppressing the Constitution’s aspirations. Secondly, the City authorities’ efforts to facilitate the hawkers’ right to the city remain ambivalent or dependent on the whims of the serving governor. Thirdly, initiatives by other actors remain elitist, topdown and opaque with only the superficial involvement of hawkers. On their part, hawkers’ initiatives to claim their right to the city have suffered from fragmented leadership and individualistic self-help micro-strategies. Furthermore, hawkers have underutilised judicial activism as an avenue for challenging the constitutionality of the city bylaws banning hawking in the CBD. This strategy would potentially have provided a discursive platform to make their claim to the city the moral-legal claim envisaged by the Constitution.